Serologic screening and infectious diseases consultation in renal transplant candidates for measles, mumps, rubella and varicella - Seckin Zeynep Idil; Libertin Claudia R.; Brumble Lisa M. (Sciendo, 2021)
Background. Renal transplant recipients are at increased risk for developing complications of vaccine-preventable diseases. They benefit from a comprehensive pre-transplant evaluation when they might safely receive live vaccines. The primary aim of our study was to investigate the number of renal transplant recipients who were evaluated for serologic status against measles, mumps, rubella (MMR), and varicella. Secondarily, we investigated if pre-transplant Infectious Diseases consultation (IDC) improved vaccination rates.